Modeling of mechanical treatment of napiform onion to determine the rational parameters of its cleaning - Tereshkin, Oleg; Horielkov, Dmytro; Dmytrevskyi, Dmytro; Chervonyi, Vitalii (Eastern-European Journal of Enterprise Technologies, 2016)
In order to improve quality of the process of cleaning vegetable raw materials, development of new equipment is necessary, which will allow processing different kinds of raw materials and manufacturing products with stable quality indicators. When designing new equipment, it is necessary to take into account that the new machinery should have compact dimensions, be versatile and multioperational. This will make it possible to successfully compete in the domestic and international markets. We designed an experimental installation with appropriate methodology that allows studying the process of cleaning napiform onion with the capacity to determine the impact of all its parameters on the percentage of loss of raw materials and efficiency of cleaning the product. This is provided for by the presence of a working drum that rotates around its axis in an experimental set-up. The rotation frequency may be changed in the required range. The working drum has at its surface special openings for cutting inedible part of the bulbs. A mathematical model of treating napiform onion during cleaning was obtained. Mathematical model takes the form of a system of inequalities, which links the coefficient of filling the drum and central angle of the segment with product. The model proves that the optimal mode of motion of the product in the drum device for cleaning is the mode under which a layer of bulbs lose equilibrium state and there occur sliding forces relative to the inner surface of the drum, which, together with the force of friction, determine the effort for cutting the neck and stem of a bulb. We received equations to calculate the limiting modes of motion when moving in the drum, which explicitly take into account the friction coefficient, angle of natural bevel of the layer of product and the magnitude of drum load. It was established that the maximum value of degree of cleaning the bulbs is 88…98 %. Mathematical modeling of the process of mechanical treatment of napiform onion allows us to determine rational parameters of the combined process of its cleaning. These parameters include rotation frequency of the working drum, load factor of the working chamber and the shape of openings in the working drum. On the basis of the conducted theoretical and experimental research, we designed a device for the combined cleaning of napiform onion. The device allows thermal pre-treatment of raw materials with the aim of weakening the bond between husk and a bulb. Subsequent mechanical treatment, which is also implemented in the device, provides complete cleaning of the product from husk.